Immune checkpoint molecules in neuroblastoma: A clinical perspective. (November 2022) - Pathania, Anup S.; Prathipati, Philip; Murakonda, Swati P.; Murakonda, Ajay B.; Srivastava, Ankit; Avadhesh,; Byrareddy, Siddappa N.; Coulter, Don W.; Gupta, Subash C.; Challagundla, Kishore B.
Abstract: High-risk neuroblastoma (NB) is challenging to treat with 5-year long-term survival in patients remaining below 50% and low chances of survival after tumor relapse or recurrence. Different strategies are being tested or under evaluation to destroy resistant tumors and improve survival outcomes in NB patients. Immunotherapy, which uses certain parts of a person's immune system to recognize or kill tumor cells, effectively improves patient outcomes in several types of cancer, including NB. One of the immunotherapy strategies is to block immune checkpoint signaling in tumors to increase tumor immunogenicity and anti-tumor immunity. Immune checkpoint proteins put brakes on immune cell functions to regulate immune activation, but this activity is exploited in tumors to evade immune surveillance and attack. Immune checkpoint proteins play an essential role in NB biology and immune escape mechanisms, which makes these tumors immunologically cold. Therapeutic strategies to block immune checkpoint signaling have shown promising outcomes in NB but only in a subset of patients. However, combining immune checkpoint blockade with other therapies, including conjugated antibody-based immunotherapy, radioimmunotherapy, tumor vaccines, or cellular therapies like modified T or natural killer (NK) cells, has shown encouraging results in enhancing anti-tumor immunity in the preclinical setting. An analysis of publicly available dataset using computational tools has unraveled the complexity of multiple cancer including NB. This review comprehensively summarizes the current information on immune checkpoint molecules, their biology, role in immune suppression and tumor development, and novel therapeutic approaches combining immune checkpoint inhibitors with other therapies to combat high-risk NB.